2021
DOI: 10.1039/d0ob02484h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of sensitive coumarin-based fluorogenic substrates for discovery of α-N-acetyl galactosaminidases through droplet-based screening

Abstract: Synthesis of sensitive coumarin α-GalNAc glycosides as substrates for droplet-based screening of GalNAcases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…We synthesized the seven fluorogenic thioglycoside substrates shown in Fig. 2, based on β-glucose, β-galactose, α-mannose, β-glucuronic acid, 4,5-unsaturated β-glucuronic acid, β-N-acetylglucosamine and β-6-phosphoglucose, based on previously reported methods 7,11 and as described in the SI (Schemes S1-4). These substrates cover a broad spectrum of commonly occurring glycosides as well as two ( 5 and 7 ) as controls since enzymes from GH4 (6-phospho-β-glucosidase) and/or GH88/105 (α-4-5-ene-glucuronidase) were likely to be present in our libraries.…”
Section: Resultsmentioning
confidence: 99%
“…We synthesized the seven fluorogenic thioglycoside substrates shown in Fig. 2, based on β-glucose, β-galactose, α-mannose, β-glucuronic acid, 4,5-unsaturated β-glucuronic acid, β-N-acetylglucosamine and β-6-phosphoglucose, based on previously reported methods 7,11 and as described in the SI (Schemes S1-4). These substrates cover a broad spectrum of commonly occurring glycosides as well as two ( 5 and 7 ) as controls since enzymes from GH4 (6-phospho-β-glucosidase) and/or GH88/105 (α-4-5-ene-glucuronidase) were likely to be present in our libraries.…”
Section: Resultsmentioning
confidence: 99%
“…This poses a hitherto unsolved challenge for fluorogenic NAD(P)H quantification as resorufin, the sole published fluorogenic probe for NAD(P)H detection [49,53] , is hydrophobic and consequently only compatible with very short reaction times in microfluidic droplets [54] . Previous work has shown that adding charged groups to fluorophores [52] and specifically coumarins [12,55] mitigates droplet leakage and improves aqueous solubility. Therefore, to prevent leakage of tSNAP and its fluorophore product 2 , a carboxylic acid group was incorporated to impart a negative charge on the coumarin scaffold at physiological pH, enabling leakage-free application in droplet microfluidics.…”
Section: Resultsmentioning
confidence: 99%
“…This facilitates the detection of these compounds in biological systems by both flow cytometry and confocal microscopy. Because the p K a of the phenol of 7OHCCA is 7.0–7.5, its brightness under physiological conditions can be enhanced by fluorine and other electron-withdrawing groups that increase its acidity . In the fluorophore Pacific Blue (PB, 2 ), fluorination at the 6- and 8-positions reduces the p K a of the phenol to 4.7 (3.7 for PB methyl ester), providing a superior low-molecular-weight fluorophore for studies of labeled proteins and small molecules .…”
mentioning
confidence: 99%
“…Because the p K a of the phenol of 7OHCCA is 7.0–7.5, its brightness under physiological conditions can be enhanced by fluorine and other electron-withdrawing groups that increase its acidity . In the fluorophore Pacific Blue (PB, 2 ), fluorination at the 6- and 8-positions reduces the p K a of the phenol to 4.7 (3.7 for PB methyl ester), providing a superior low-molecular-weight fluorophore for studies of labeled proteins and small molecules . However, when used to study interactions of small molecules with intracellular proteins in live cells, we have found that PB derivatives are often efficient substrates of efflux transporters such as p-glycoprotein (MDR1). This high susceptibility to active cellular efflux mechanisms can reduce the ability of related molecular probes to engage intracellular targets in the absence of efflux inhibitors such as verapamil …”
mentioning
confidence: 99%
See 1 more Smart Citation